"Información, ansiedad y depresión en el cuidador primario del paciente con enfermedad renal crónico terminal. 2013" - Cotrina Morales, Lesly Katheryn (2013)
Investigation quantitative-descriptive type and transactional correlational design, which was made to determinate the relation between level of information, angst and depression in the primary caregiver of the patient with chronic kidney disease terminal. The size of the samples was constituted for 120 primary caregiver, which is extracted a representative sample of 50; the instrument used was: The quiz to evaluate the level of information of primary caregiver of the patient with chronic kidney disease terminal, made by authors and the angst and depression scale of Golberg. To processing of information use was made of program SPSS V.21. To determinate the relation between variables gamma test was used, was considered significant the relation if the value p was less than 0.5. The results found that 50 percent of primary caregiver have regular level of information, followed by 46 percent level 4 percent level good and bad, 86 percent of primary caregivers are identified as probable cases of anxiety and 72 percent are identified as probable cases of depression. No statistically significant relationship was found between anxiety and depression with the information level (p value> 0, 05).